A Screening Method Using LC-MS MS for Illicit Drugs in Postmortem Blood an Application to 62 Postmortem Cases - Akgür, Serap Annette; Dolma, Ceyhun; Ertaş, Hasan; Teker, Ceyda; Moral, Ali Reşat (The Bulletin of Legal Medicine, 2007)
Screening of biological specimens in the presence of illicit drugs is of great importance, particularly in criminal cases. The most relevant matrices to be analyzed for this purpose are plasma or blood, due to providing a good correlation between their concentration and pharmacological effects. For majority of laboratories, a common method for screening illicit drugs has been immunoassay methods and Gas Chromatography-coupled with Mass Spectrometry (GC-MS) that is widely employed for confirmation purposes. However, the widespread use of liquid chromatography coupled single-stage or tandem mass spectrometry (LC-MS, LC-MS/MS) is becoming increasingly significant for both qualitative and quantitative analysis of target analyse which could be polar and thermally labile. This assay method, consisted of morphine, (±)-amphetamine, (±)-methamphetami-ne, cocaine, benzoylecgonine, cocaethylene and (-)-ll-nor-9-car-boxy-c9-THC was based on the detection of LC-ESI-MS. In this study, LC-MS/MS method for illicit drugs in postmortem blood was developed. These data provided a documentation to use LC-MS/MS technique without any precipitation for postmortem blood to detect low concentrations of some illicit drugs and applied to 62 postmortem forensic cases.Key words: Illicit drug, screening, LC-MS/MS, postmortem blood
Keywords: illicit drug; screening; lc-ms; ms; postmortem blood